Text mining for disease surveillance in veterinary clinical data: part one, the language of veterinary clinical records and searching for words - Davies, Heather; Nenadic, Goran; Alfattni, Ghada; Arguello Casteleiro, Mercedes; Al Moubayed, Noura; Farrell, Sean O.; Radford, Alan D.; Noble, Peter-John M. (Frontiers in Veterinary Science, 2024)
The development of natural language processing techniques for deriving useful information from unstructured clinical narratives is a fast-paced and rapidly evolving area of machine learning research. Large volumes of veterinary clinical narratives now exist curated by projects such as the Small Animal Veterinary Surveillance Network (SAVSNET) and VetCompass, and the application of such techniques to these datasets is already (and will continue to) improve our understanding of disease and disease patterns within veterinary medicine. In part one of this two part article series, we discuss the importance of understanding the lexical structure of clinical records and discuss the use of basic tools for filtering records based on key words and more complex rule based pattern matching approaches. We discuss the strengths and weaknesses of these approaches highlighting the on-going potential value in using these 'traditional' approaches but ultimately recognising that these approaches constrain how effectively information retrieval can be automated. This sets the scene for the introduction of machine-learning methodologies and the plethora of opportunities for automation of information extraction these present which is discussed in part two of the series.